2015
DOI: 10.1177/0004867415595290
|View full text |Cite
|
Sign up to set email alerts
|

Self-enucleation and the real meaning of Oedipus

Matthew Large

Abstract: The guidelines are excellent; but real advocacy is required too. It is good for patients, and for us.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…But it may not be correct to solely implicate Christian teachings for the incidence of oedipism. [ 1 2 4 5 ] Self-enucleation has also been reported among non-adherents of Christianity. Aksray et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…But it may not be correct to solely implicate Christian teachings for the incidence of oedipism. [ 1 2 4 5 ] Self-enucleation has also been reported among non-adherents of Christianity. Aksray et al .…”
Section: Discussionmentioning
confidence: 97%
“…Thus, published works on the subject continue to be case reports on one or two cases with uniocular involvement predominating. [ 1 2 4 5 13 16 17 ] An extensive literature search, via MEDLINE, reported that there were 37 published papers on the subject. [ 1 ] These papers documented 56 patients (71 globes) worldwide who had auto-enucleation in at least one eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is traditionally referred to as oedipism, in reference to the Greek play Oedipus Rex, in which the Theban King Oedipus gouges out his eyes in an attempt to "cleanse" himself after killing his father and marrying his mother. [1][2][3] It is considered a form of selfmutilation alongside the amputation of body parts, such as the upper limbs or genitalia. 4 Self-enucleation is commonly associated with psychotic paranoid delusion, either functional, which is mainly associated with schizophrenia, or drug induced, related to alcohol, lysergic acid diethylamide, or amphetamines.…”
mentioning
confidence: 99%